Evaluation of Serum Vaspin and Chemerin Levels in Type 2 Diabetic and Treated with Anti Diabetic Drugs Metformin and Acarbose in Rats - Seyed Mohammad Ali Ghaffari; Mohammad taghi Mansouri; Mohammad Hossein Haghighizadeh; Elham Rafie (Fasa University of Medical Sciences, 2015)
Background & Objective: The serum levels of adipose tissue hormons, Vaspin and Chemerin, alter in some disorder conditions such as diabetes. The aim of this study is to investigate the effect of two anti-diabetic drugs (Metformin and Acarbose) and their combination on serum concentration of Vaspin and Chemerin in type 2 diabetic rats.   Materials & Methods: 30 male, wistar rats are randomly divided into 5 groups, while 4 groups are suffered from type 2 diabetes, and 3 groups of these diabetics are cured using metformin, acarbose, and combination of both, respectively, during 6 weeks. Body weight, fasting glucose, glycated hemoglobin, lipid profile, and serum's vaspin and chemerin are being examined. Statistic data are analyzed using SPSS software. Results report by mean ± standard deviation, and statistic difference considers significant by P˂0.05.   Results: Findings of this study show a significant decrease for vaspin (P=0.001) and a significant increase for chemerin levels (P=0.004) in diabetic control group compared with normal control group. Treatment of all groups show a significant increase in serum levels of vaspin (P=0.001) while treatment by metformin results in a significant decrease in chemerin level in this group (P=0.036). In this study, fasting blood glucose, glycated hemoglobin, and lipid profile in treated group with both of drugs show decrease that is more significant.   Conclusion: Probably metformin and acarbose through increase of serum level of vaspin leads to reduction of insulin resistance.